Quality of marital relationship and depression: Results of a 10-year prospective follow-up study - Kronmüller, Klaus-Thomas; Backenstraß, Matthias; Victor, Daniela; Postelnicu, Ilinca; Schenkenbach, Caroline; Joest, Katharina; Fiedler, Peter; Mundt, Christoph (Journal of affective disorders, 2011)
Background: - Although the long-term course of depression has been intensively examined, there are only few studies on the long-term development of depressed patients' spousal relationships. The aim of the study was to assess the quality and stability of depressed patients' spousal relationships in the long-term course of depression and to identify predictors of relationship outcome. - Methods: - In the study, 50 inpatients with Major Depression were followed-up one, two and ten years after discharge from hospital and compared to a healthy control group matched by age and sex. Marital satisfaction was measured by the Terman item. Expressed Emotion (EE) was assessed with the Five-Minute Speech Sample (FMSS) and the Perceived Criticism Index (PC). - Results: - In the follow-up period of ten years, 26 patients (56.5%) had a recurrence. Ten years after discharge from hospital 8 couples were separated, 11 were unhappy and 26 couples were happy with their spousal relationship. The quality of marital relationship decreased over the follow-up period. In comparison to a healthy control group, patients showed a significantly worse quality of marital relationship at follow-up. Besides age and course of depression, the spousal EE status was a prognostic factor for the quality of the relationship after 10years. - Conclusions: - The results confirm the decrease of marital satisfaction over time in the long-term course of depression. Identified interpersonal predictors of the quality of spousal relationship in major depression could be used as indication criteria for couple therapy.
Available online 2 August 2010
Gesehen am 11.07.2022